Applying Conflict Management Strategies to the Pediatric Operating Room. (October 2019) - Sinskey, Jina L.; Chang, Joyce M.; Shibata, Gail S.; Infosino, Andrew J.; Rouine-Rapp, Kathryn
Abstract : Effective communication is essential in today's health care environment, and poor communication can lead to conflict among health care providers. Differences in cultures and beliefs can further incite conflict among health care team members, families, and patients. Pediatric patient care has a higher potential for conflict because decision-making responsibilities are shared among patients, parents/guardians, and clinicians. It is important to understand the phases and types of conflict because each conflict situation requires a different approach to optimize management. Equally important is an understanding of styles used by individuals to manage conflict. The Thomas–Kilmann Conflict Mode Instrument and the Dutch Test for Conflict Handling are 2 validated tools used to assess conflict management styles. The different styles include competing/forcing, collaborating/problem solving, compromising, avoiding, and yielding/accommodating. A successful physician should be able to identify the phases and types of conflict to use the conflict management approach most suitable for the given conflict. There are several techniques for managing conflict in the pediatric operating room. Acknowledging and managing one's own emotions during conflict is a pivotal first step toward diffusing the situation. Active listening is an important communication skill that improves team dynamics. Aligning the interests of the parties involved in conflict will encourage collaborative problem solving. Cultural competency training can improve communication and conflict management skills. Effective conflict management through formal education of all perioperative team members can lead to improved communication and teamwork and better patient outcomes.